Periodic-peristole agitation for process enhancement of butanol fermentation - Xia, Meng-lei (Biotechnol Biofuels, 2015)
BACKGROUND: Mass transfer plays an important role in determining the efficiency of the biofuel conversion. However, adverse effect of shear stress from traditional agitation inhibits the cell growth and production of biofuels. How to enhance the mass transfer with less adverse effect is considered as one of the important bioengineering issues. RESULTS: In this study, a novel agitation type, named periodic-peristole was applied to butanol fermentation with Clostridium acetobutylicum ATCC 824. Meanwhile, the enhancement mechanism was studied. Initially, the fermentation performance of periodic-peristole agitation was compared with the traditional Rushton impeller and stationary cultivation. Result showed that the biomass, butanol and total solvent in periodic-peristole group (PPG) was enhanced to 1.92-, 2.06-, and 2.4-fold of those in the traditional Rushton impeller group (TIG), as well as 1.64-, 1.19- and 1.41-fold of those in the stationary group (SG). Subsequently, to get in-depth insight into enhancement mechanism, hydromechanics analysis and metabolic flux analysis (MFA) were carried out. The periodic-peristole agitation exhibits significant difference on velocity distribution, shear force, and mixing efficiency from the traditional Rushton impeller agitation. And the shear force in PPG is only 74 % of that in TIG. According to MFA result, fructose 6-phosphate, pyruvate, acetyl-CoA, oxaloacetate and α-ketoglutarate were determined the key nodes of cells in response to hydrodynamic mechanical stress. Based on such key information, rational enhancement strategies were proposed and butanol production was further improved. CONCLUSION: The agitation associated with three issues which resulted in significant changes in cell metabolic behaviors: first, a rebalanced redox status; second, the energy (ATP) acquirement and consumption; third, the tolerance mechanism of the cell for survival of solvent. Periodic-peristole agitation provides an answer to address a long-standing problem of biofuel engineering. Key information derived from current study deepens the understanding of agitation, which can guide the designment of new bioreactors and development of enhancement strategies for biofuel refinery. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-015-0409-6) contains supplementary material, which is available to authorized users.